1999
DOI: 10.1046/j.1469-7580.1999.19540563.x
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric and ultrastructural changes with ageing in mouse peripheral nerve

Abstract: Qualitative and quantitative information is reported on the morphological changes that occur in nerve fibres and nonneuronal cells of peripheral nerve during the lifetime of the mouse. Tibial nerves of mice aged 6-33 mo were studied. With ageing, collagen accumulates in the perineurium and lipid droplets in the perineurial cells. Macrophages and mast cells increase in number, and onion bulbs and collagen pockets are frequently present. Schwann cells associated with myelinated fibres (MF) slightly decre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
157
0
8

Year Published

2001
2001
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 161 publications
(175 citation statements)
references
References 40 publications
10
157
0
8
Order By: Relevance
“…Indeed, the lower density of immunolabeled TRPV1-positive fibers in tibial and cutaneous nerves would support this possibility. However, anatomical studies have indicated that loss of afferents in the skin becomes most prominent only in very old animals [13]. Only a modest afferent loss would therefore be expected at 15 months of age, the time at which a reduction in TRPV1 protein was measured in this study.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…Indeed, the lower density of immunolabeled TRPV1-positive fibers in tibial and cutaneous nerves would support this possibility. However, anatomical studies have indicated that loss of afferents in the skin becomes most prominent only in very old animals [13]. Only a modest afferent loss would therefore be expected at 15 months of age, the time at which a reduction in TRPV1 protein was measured in this study.…”
Section: Discussionmentioning
confidence: 62%
“…Functional studies in several species have shown that impairment of cutaneous sensitivity occurs with aging [13,37]. This age-related decrease in sensitivity can reduce tactile perception, detection of noxious stimuli and tissue injury.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, we monitored myelinated (A‐fibers) density in p‐phenylene diamine (PPD)‐stained sections. In agreement with previous studies (Ceballos et al ., 1999), two‐way ANOVA showed an aging effect [ F 1,16  = 11.71, p = 0.0038] with aged animals exhibiting reduced density of myelinated fibers independently of genotype (p < 0.05 for both genotypes) (Fig. 2A,B).…”
Section: Resultsmentioning
confidence: 97%
“…Age-related changes in the neuronal soma size (Liu et al ., 1996;Kanda & Hashizume, 1998) and number (Hashizume et al ., 1988;Zhang et al ., 1996;Jacob, 1998) in the spinal cord have been reported. Age-related changes in peripheral nerve have been documented in tibialis nerves of mice aged 6 -33 months (Ceballos et al ., 1999) including accumulation of collagen in the perineurium and lipid droplets in the perineurial cells, together with an increase in the number of macrophages and mast cells. Schwann cells associated with myelinated fibres (MF) decrease slightly in number, in parallel with an increase of the internodal length from 6 to 12 months, but then increase in number in older nerves in parallel with the greater incidence of demyelination and remyelination.…”
Section: Effects Of Age On the Neuromuscular Junctionmentioning
confidence: 99%